TOXICITY TEST OF DAYAK ONION BULBS EXTRACT (Eleuthherine palmifolia (L) Merr) ON Artemia salina LEACH USING BSLT METHOD (Preface Study As Root Canal Irrigation Materials) - Khairunnisa, Khairunnisa; Ichrom Nahzi, Muhammad Yanuar; Diana, Sherli (FKG Unlam, 2018)
Background: Dayak onion (Eleutherine palmifolia (L) Merr) is a native plant from Central Kalimantan, which contains active compounds as anti-bacterials that can be used as an alternative material for root canal irrigation. High toxicity is one of the causes of root canal failure, so it takes a toxicity test to determine the toxic effects of the dayak onion bulbs extract. Purpose: To analyze the difference of toxic effects with various concentrations of dayak onion bulbs extract on Artemia salina Leach using BSLT method. Material and Methods: This study used true experimental research design, namely post-test only with control group design treated with 11 different treatments, which were dayak onion bulbs extract with concentrations 10 mg/ml, 20 mg/ml, 30 mg/ml, 40 mg/ml, 50 mg/ml, 60 mg/ml, 70 mg/ml, 80 mg/ml, 90 mg/ml, 100 mg/ml and sea water as its negative control, and done with 3 times repetitions. Result: The result of the probit analysis in the amount of LC50 was 70,371 mg/ml. The data analysis used Shapiro-Wilk and Leveneâs Test results p > 0,05 means that all the data was normally distributed and homogenous. Further test with One Way Anova obtained result p < 0,05 which means there was a significant difference in the number of dead larvae between concentrations. Further test with Pos-hoc LSD obtained result that there was a significant difference at concentration 100 mg/ml with 10 mg/ml with value p=0,001. Conclusion: The highest toxic effect on dayak onion bulbs extract on Artemia salina Leach is at concentration of 100 mg/ml.